PELATIHAN KETERAMPILAN KOMUNIKASI POKDARWIS DESA WISATA MENDAK KECAMATAN DAGANGAN MADIUN - Widiantari, Maria Magdalena (Universitas Merdeka Madiun, 2019)
Abstractâ€” Communication skills for Kelompok Sadar Wisata (Pokdarwis- Tourism Awareness Groups) are important because they are related to best services for visitors and to ensure the continuity of tourism visitation..Communication skills are not only related with manner, but also related with how to build a cooperation with other parties, tourism marketing, and tourism branding in mass media. The training will be divided into several materials, namely communication skills in general terms, public speaking, mass media marketing and branding, and lobbying-negotiating for cooperation building with other parties. The purpose is that the members of the Pokdarwis have good communication skills so they can support the development of Watu Rumpuk tourist destinations and conduct profitable cooperation with various national tourism bureaus so as to increase the number of visits and in turn improve the welfare of rural communities.Â Keywordsâ€”: communication, Pokdarwis, Watu Rumpuk, Mendak.